Extortion and Civic Engagement among Guatemalan Deportees - Denny, Elaine K.; Dow, David; Levy, Gabriella; Villamizar-Chaparro, Mateo (World Bank, Washington, DC, 2022)
How does extortion experienced during the migration journey affect the civic engagement of deported migrants returned to their home country? More broadly, how does extortion affect political participation? Little is known about either the political behavior of returnees or about how coercive economic shocks experienced during migration affect subsequent levels of political participation. More broadly, existing literature on how victimization affects political participation is inconclusive, particularly when combined with existing work on economic insecurity. Studying deported migrants and the quasi-random experience of extortion helps address the endogeneity that often confounds these analyses. This approach isolates the impact of extortion on political action from potentially confounding factors related to local security or corruption. Using a novel dataset concerning Guatemalan migrants returned to Guatemala by the U.S. government, this paper finds that extortion has a direct, positive relationship with multiple forms of civic action, and that, at least in this context, the mobilizing effects of economic hardship outweigh the potentially demobilizing effects of fear of crime.